23‐1: Invited Paper: Single and Tandem OLED Display Technologies with High Efficiency and Long Lifetime. Issue 1 (28th June 2021) - Mizusaki, Masanobu; Shibasaki, Masakazu; Tsukamoto, Yuto; Umeda, Tokiyoshi; Kawato, Shinichi; Nakamura, Kei; Tahara, Tetsuya; Yamamoto, Keiichi; Haseba, Yasuhiro; Shimada, Shinji
Abstract : RGB side‐by‐side (SBS) top‐emission (TE) flexible OLED display with high efficiency and long lifetime has been developed for mobile and automotive applications. We have firstly developed a high reliability single‐type OLED display with a lifetime over 1, 000 hours under 900 cd/m2 driving at 85 °C and with wide color gamut (over 110% of NTSC ratio). This is especially useful for the automotive displays. In addition, we have also focused on a blue TE tandem OLED for improving the current efficiency and achieved the blue index of 320 with two‐stacked tandem OLED. This is 1.6 times larger than that of the blue single‐type OLED.